Foreign Capital Inflows and Growth: An Empirical Analysis of WAMZ Experience - Anthony . Orji; Akachukwu Stanley Uche; Elijah Ayobami Ilori (International Journal of Economics and Financial Issues, 2014)
Using the Seemingly Unrelated Regression Estimation (SURE) technique, we examine the implications of four different types of foreign capital inflows, namely; Foreign Direct Investment (FDI), Official Development Assistance (ODA), Foreign Private Investment (FPI) and Remittances (REM) on output growth of the West Africa Monetary Zone (WAMZ) economies over the period 1981-2010. Our results show that there are differences in the growth impact of the various forms of foreign capital inflows in the WAMZ countries. The result also shows that more than one form of capital inflow contributed positively to output growth in Nigeria. Again, we find that ODA positively contributes more to output growth in Sierra Leone and Ghana, whereas, FDI foster more output growth in Nigeria and Gambia.  Remittances have the highest contribution in Liberia and finally none of the inflows has positively impacted on Guinea’s economic growth. We therefore recommend that WAMZ countries should endeavor to create competitive economic environments that will be attractive to foreign investors since promoting trade and investment through sound economic policies and strengthened institutions are essential in maximizing the benefits from Foreign Capital Inflows in the region.